2021
DOI: 10.3389/fcell.2021.775642
|View full text |Cite
|
Sign up to set email alerts
|

HIF-1α Induces HECTD2 Up-Regulation and Aggravates the Malignant Progression of Renal Cell Cancer via Repressing miR-320a

Abstract: Renal cell carcinoma (RCC) is a frequent malignancy of the urinary system. It has been found that hypoxia mediates the malignant evolvement of RCC. Here, we probe the impact and potential mechanism of HECT domain E3 ubiquitin-protein ligase 2 (HECTD2) and HIF-1α on regulating RCC evolvement. RCC tissues and adjacent normal tissues were collected, and the association between the expression profiles of HECTD2 and HIF-1α and the clinicopathological features was analyzed. Additionally, we constructed HECTD2/HIF-1α… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 50 publications
(44 reference statements)
1
3
0
Order By: Relevance
“…In colorectal cancer cells, HECTD2 overexpression induces LPCAT1 ubiquitination and degradation, inhibiting tumor cell proliferation (28). In RCC cells, by weakening miR-320a, HIF-1α increases the expression of HECTD2, boosting tumor cell proliferation, migration, invasion, and EMT while decreasing apoptosis and hastening the malignant development of cancer cells (29). We saw up-regulated HECTD2 in RCC through clinical analysis, which is consistent with previous research.…”
Section: Discussionsupporting
confidence: 90%
“…In colorectal cancer cells, HECTD2 overexpression induces LPCAT1 ubiquitination and degradation, inhibiting tumor cell proliferation (28). In RCC cells, by weakening miR-320a, HIF-1α increases the expression of HECTD2, boosting tumor cell proliferation, migration, invasion, and EMT while decreasing apoptosis and hastening the malignant development of cancer cells (29). We saw up-regulated HECTD2 in RCC through clinical analysis, which is consistent with previous research.…”
Section: Discussionsupporting
confidence: 90%
“… 36 More recent data revealed that HIF-1α could upregulate HECT domain E3 ubiquitin-protein ligase 2, a target gene of miR-320a, in renal cells. 37 Preliminary results in our study indicated that lncNEAT1 and HIF-1α could competitively bind to miR-320a, and lncNEAT1 could upregulate HIF-1α expression by inhibiting miR-320a. Therefore, we further speculated that lncNEAT1/miR-320a might act as a ceRNA network to jointly regulate HIF-1α and affect the invasion, migration and permeability of ARPE-19 cells.…”
Section: Discussionmentioning
confidence: 57%
“…KEGG analysis showed that DEGs were mainly enriched in the HIF-1 signaling pathway, glycolysis/gluconeogenesis signaling pathway, COVID-19 signaling pathway, and ribosome-related signaling pathway. It has been demonstrated that HIF-1 can hinder miR-32's upregulation of HECTD2, hence accelerating the progression of renal carcinoma (Lv et al, 2021). A poor prognosis is typically predicted by elevated HIF1 in ccRCC (Gudas et al, 2014).…”
Section: Discussionmentioning
confidence: 99%